Investigación sobre los estilos de enseñanza. Aportes para mejorar la didáctica de Ciencias - Ventura, Ana Clara (2014)
The aim of this paper is to clarify conceptual and operational aspects of the construct “teaching styles” with its three distinctive properties: relative stability, multidimensionality and value neutrality. Moreover, it analyzes the points of view that are shared for many empirical studies: teachers transmit knowledge and typical forms of learning; teaching styles differ according to the type of subject taught, the match between the teaching styles and learning styles improve knowledge acquisition. In summary, this paper provides knowledge and strategies that contribute to training in science teaching and, therefore, to strengthen effective teaching practices.